The Shifting Aesthetics of Expertise in the Sharing Economy of Scientific Medicine. Issue 1 (27th March 2018) - Ostherr, Kirsten
Argument: The deficit model of science communication assumes that the creation and dissemination of knowledge is limited to researchers with formal credentials. Recent challenges to this model have emerged among "e-patients" who develop extensive online activist communities, demand access to their own health data, conduct crowd-sourced experiments, and "hack" health problems that traditional medical experts have failed to solve. This article explores the aesthetics of medical media that enact the transition from a deficit model to a patient-driven model of visual representation and health communication. I present a framework for understanding the role of film and video in patient movements by analyzing the historical transition from researchers filming patients as nameless, voiceless human research subjects to patients recording their own health narratives through activist cinematography. By comparing several approaches to patient-centered video, I argue that imperfect production aesthetics play a critically important role in establishing the credibility of health communications.